The Effect of Ownership Structure and Environmental Costs on Financial Performance With Company Characteristics and Cost Efficiency as Intervening Variables in Metal and Similar Sub-Sector Companies Listed on the Indonesia Stock Exchange - Marcelia Adriana; Hwihanus (Business and Investment Review, 2025)
This study is focused on investigating and evaluating the impact of Ownership Structure and Environmental Costs on Financial Performance using Company Characteristics and Cost Efficiency as Intervening Variables. All companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024 that are part of the Metal and Similar Sub-Sector comprise the population used in this study. The Partial Least Square (PLS) method, which incorporates testing through the outer model and inner model, was used for data analysis and hypothesis testing. The study's findings show that ownership structure negatively influences financial performance, although the effect is not statistically significant. Meanwhile, ownership structure shows a positive and significant influence on company characteristics, and a negative yet significant influence on cost efficiency. Furthermore, environmental costs positively affect company characteristics but without significance, and they also negatively influence financial performance, although not significantly. In addition, company characteristics demonstrate a positive and significant effect on cost efficiency, while cost efficiency itself positively and significantly contributes to financial performance.